Soybean Cost-Return Budget in Southeast Kansas - Fogleman, Sarah L.; Kilgore, Gary L. (My University, 2002)
This publication outlines the expected costs and returns for soybean production in southeast Kansas.
MF994_2002_10
Keywords: MF994; Economics; Crops; MF